Integrating Project-Based Learning and Deep Learning Principles to Foster Speaking Fluency and Critical Thinking in EFL - Rampeng Rampeng; Restu Januarty Hamid; Rosmawati Abdul Maing; Sujariati Sujariati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study investigates how integrating Project-Based Learning (PBL) with deep learning principles can simultaneously improve speaking fluency and critical thinking among Indonesian EFL learners. Recognizing that these two competencies are mutually reinforcing yet rarely taught together, a Project-Based Deep Learning (PBDL) model was implemented across three educational institutions involving 180 students. The study employed a quasi-experimental design to examine the model’s impact on learners’ oral performance and analytical reasoning. Findings revealed substantial improvements in both speaking fluency and critical thinking, with the strongest gains observed in discourse management and analytical reasoning. More importantly, students who engaged in authentic, problem-driven projects and received iterative feedback demonstrated greater confidence, coherence, and reflective judgment in communication tasks. These outcomes suggest that PBDL not only enhances linguistic proficiency but also fosters deeper cognitive engagement, helping learners connect language use with reasoning and decision-making. The study provides empirical and practical insights for EFL teachers, emphasizing that authentic tasks, collaboration, and structured reflection can transform traditional classrooms into active learning environments that cultivate integrated 21st-century skills.